Dynamics of bone graft healing around implants - Narayan Venkataraman; Sumidha Bansal; Pankaj Bansal; Sarita Narayan (Wolters Kluwer Medknow Publications, 2015)
Bone is a highly dynamic tissue undergoing constant adaptation to the mechanical and metabolic demands of the body by bone regeneration and repair. In order to facilitate or promote bone healing, bone grafting materials have been placed into bony defects. The advantages of using bone grafts are space maintenance, inhibiting collapse of defect and acting (at least) as osteoconductive scaffold (though they can be osteoinductive or osteogenic also). After their successful use around teeth afflicted by periodontal disease, in ridge augmentations, and in socket preservations, we now look forward to their use around implants during the osseointegration phase. A few questions arise pertaining to the use of bone grafts along with implants are whether these are successful in approximation with implant. Do they accelerate bone regeneration? Are all defects ultimately regenerated with new viable bone? Is the bone graft completely resorbed or integrated in new bone? Does the implant surface characteristic positively affect osseointegration when used with a bone graft? What type of graft and implant surface can be used that will have a positive effect on the healing type and time? Finally, what are the dynamics of bone graft healing around an implant? This review discusses the cellular and molecular mechanisms of bone graft healing in general and in vicinity of another foreign, avascular body, namely the implant surface, and further, the role of bone grafts in osseointegration and/or clinical success of the implants.